2007
DOI: 10.1159/000103997
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Sensitization to Fungal Enzymes Used in Animal Feed Industry

Abstract: Background: Industrial enzymes cause the increasing prevalence of occupational hypersensitivity. Our objective was to study workers occupationally exposed to fungal enzymes in 2 animal feed factories to determine if the sensitization originated in the enzymes or was caused by the microorganism used to produce the enzymes. Methods: Eighty-six consenting workers were studied by skin prick tests with extracts from the enzymatic products handled in their factories. Positive workers were then studied by IgE immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…The approximately 130 described species of Trichoderma are dispersed to all latitudes, habitats, and climatic zones (Klein and Eveleigh 1998). They are usually encountered in soils (Domsch et al 2007;Klein and Eveleigh 1998), but may also colonize diverse habitats such as water-damaged building materials or indoor dust (Thrane et al 2001), mushroom production facilities (Komon-Zelazowska et al 2007;Samuels et al 2002), animal feed (Caballero et al 2007), marine sponges (Sperry et al 1998), and sapwood of trees (Evans et al 2003). Trichoderma species are used in the biological control of plant disease and as stimulators of plant growth (Harman et al 2004), while some species are able to degrade polysaccharides and related macromolecules (Bénitez et al 1998;Bigly and Tenkanen 1998;Koivula et al 1998;Kubicek and Penttilä 1998;Lorito 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The approximately 130 described species of Trichoderma are dispersed to all latitudes, habitats, and climatic zones (Klein and Eveleigh 1998). They are usually encountered in soils (Domsch et al 2007;Klein and Eveleigh 1998), but may also colonize diverse habitats such as water-damaged building materials or indoor dust (Thrane et al 2001), mushroom production facilities (Komon-Zelazowska et al 2007;Samuels et al 2002), animal feed (Caballero et al 2007), marine sponges (Sperry et al 1998), and sapwood of trees (Evans et al 2003). Trichoderma species are used in the biological control of plant disease and as stimulators of plant growth (Harman et al 2004), while some species are able to degrade polysaccharides and related macromolecules (Bénitez et al 1998;Bigly and Tenkanen 1998;Koivula et al 1998;Kubicek and Penttilä 1998;Lorito 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nine percent of subjects tested positive and were more frequently sensitized to phytase from Trichoderma sp. and Peniophora sp., but there was no description of IgE or allergy to extracts or proteins from the gene source, bacterium Bacillus amyloliquefaciens (Caballero et al, 2007). Two additional references (Saris et al, 2009;Mikkola et al, 2007) were identified that evaluated possible toxicity of amylosin, a 1197 Da toxin produced by Bacillus amyloliquefaciens strains isolated from the indoor environment of moisture-damaged buildings.…”
Section: Pubmed Search Resultsmentioning
confidence: 99%
“…O'CONNOR et al [14] have proved by specific bronchial challenge that phytase can cause occupational asthma. In addition, BAUR et al [9] confirmed that powdered phytase derived from A. niger is a highly sensitising substance and, recently, CABALLERO et al [15] showed that phytases from Peniophora and Trichoderma species caused IgE-mediated allergy in animal feed industry workers. In the present case, the sensitising phytase was an A. awamori 3-phytase expressed in T. reesei.…”
Section: Discussionmentioning
confidence: 98%